2009
DOI: 10.1097/mph.0b013e3181acd93d
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase and Arylesterase Activity With Oxidative Status in Children With Thalassemia Major

Abstract: It was seen that oxidative stress increases, while serum paraoxonase activity is decreased in BTM patients. Decrease in paraoxonase activity seems to be associated with both the degree of oxidative stress and anemia. BTM patients may be more prone to development of atherogenesis because of low serum paraoxonase/arylesterase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In β-thalassaemia major patients, increased free-radical production, peroxidative damage to tissues and depletion of endogenous antioxidants have been expected and may be a major cause of haemolysis 34. Cakmak et al reported peroxidative damage to lipids and proteins in β-thalassaemia major patients, that is, indicated by about a twofold increase in the serum MDA/thiobarbituric acid with a significant decrement in the serum TAC owing to depletion of lipid-soluble antioxidants 35. In contrast, another study found that freshly drawn red blood cells from β-thalassaemia and Eβ-thalassaemia patients do not exhibit any significant increase in the concentration of serum MDA.…”
Section: Discussionmentioning
confidence: 99%
“…In β-thalassaemia major patients, increased free-radical production, peroxidative damage to tissues and depletion of endogenous antioxidants have been expected and may be a major cause of haemolysis 34. Cakmak et al reported peroxidative damage to lipids and proteins in β-thalassaemia major patients, that is, indicated by about a twofold increase in the serum MDA/thiobarbituric acid with a significant decrement in the serum TAC owing to depletion of lipid-soluble antioxidants 35. In contrast, another study found that freshly drawn red blood cells from β-thalassaemia and Eβ-thalassaemia patients do not exhibit any significant increase in the concentration of serum MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of MS is not yet clear, inflammation plays an important role 13. Other studies indicate that oxidative stress has a major role in the etiology of MS 14. In addition, ischemia modified albumin, a highly sensitive marker for ischemia, is elevated in MS patients 15.…”
Section: Discussionmentioning
confidence: 99%
“…The assay is calibrated with hydrogen peroxide and the results are expressed in terms of micromolar hydrogen peroxide equivalent per litre (lmol H 2 O 2 equiv./L). The ratio of the total peroxide to the total antioxidant potential gives the OSI, a marker of the degree of oxidative stress [9,10].…”
Section: Measurement Of Total Oxidant-antioxidant Statusmentioning
confidence: 99%
“…The ratio of total oxidative status (TOS) level to total antioxidant status (TAS) level is regarded as the oxidative stress index (OSI). This has been used as a new marker of the degree of oxidative stress [9,10]. It has been found that OSI and TOS are increased in patients with diabetic nephropathy compared to diabetic patients without nephropathy [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation